The Ugandan morality crusade: the brutal campaign against homosexuality and pornography under Yoweri Museveni - Kintu, Deborah (McFarland & Company, Inc., Publishers, 2018)
"In 1999, with approval of sections of Uganda's clergy (and support of U.S. evangelicals) harsh morality laws were passed against pornography and homosexual acts. The author weaves together a series of vignettes and anecdotes that trace the development of Uganda's morality laws against a backdrop of Machiavellian politics, religious fundamentalism and the human rights struggle of LGBT Ugandans"--Provided by publisher